2014
DOI: 10.1099/ijs.0.064295-0
|View full text |Cite
|
Sign up to set email alerts
|

Description of Domibacillus indicus sp. nov., isolated from ocean sediments and emended description of the genus Domibacillus

Abstract: ). The genomic DNA G+C content was 37.4 mol% and the strain showed 37.7 % DNA-DNA relatedness to D. robiginosus DSM 25058 T . The major fatty acids were anteiso-C 15 : 0 , C 16 : 0 , iso-C 15 : 0 and iso-C 16 : 0 and MK-6 was the predominant quinone. The polar lipid profile of strain SD111T consisted of unidentified phospholipids (PL1 and PL2), phosphatidylglycerol (PG) and diphosphatidylglycerol (DPG). The cell wall contained mesodiaminopimelic acid and the peptidoglycan was of A1c type. Glucose and ribose we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 24 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…? oxidation , Domibacillus (Firmicutes), a gram-positive, spore-forming, aerobic, nonmotile, rod-shaped organism isolated from deep-sea sediment (Sun and Sun 2016), ocean sediment (Sharma et al 2014), mangrove sediment soil and macroalgae (Verma et al 2017) and GP1 (Acidobacteria), found in alpine grassland on the Tibetian Plateau (Yuan et al 2014). Winter samples were more characterized by extremophile but omnipresent bacteria like Bifidobacterium (Actinobacteria) that can withstand a high range of pH (from 8 to 2) (Charteris et al 1998), Vulcaniibacterium, a thermotolerant Gammaproteobacteria isolated from a geothermally heated soil (Yu et al 2013), and Polaribacter (Bacteriodetes), which has been found in several arctic habitats (Cuthbertson et al 2017;Harding et al 2011;Collins et al 2010).…”
Section: Different Seasonal Dispersal Patterns For Bacterial and Fungmentioning
confidence: 99%
“…? oxidation , Domibacillus (Firmicutes), a gram-positive, spore-forming, aerobic, nonmotile, rod-shaped organism isolated from deep-sea sediment (Sun and Sun 2016), ocean sediment (Sharma et al 2014), mangrove sediment soil and macroalgae (Verma et al 2017) and GP1 (Acidobacteria), found in alpine grassland on the Tibetian Plateau (Yuan et al 2014). Winter samples were more characterized by extremophile but omnipresent bacteria like Bifidobacterium (Actinobacteria) that can withstand a high range of pH (from 8 to 2) (Charteris et al 1998), Vulcaniibacterium, a thermotolerant Gammaproteobacteria isolated from a geothermally heated soil (Yu et al 2013), and Polaribacter (Bacteriodetes), which has been found in several arctic habitats (Cuthbertson et al 2017;Harding et al 2011;Collins et al 2010).…”
Section: Different Seasonal Dispersal Patterns For Bacterial and Fungmentioning
confidence: 99%
“…This bacterium showed 97.6% 16S rRNA gene sequence similarity with the only other species reported, i.e. Domibacillus robiginosus strain WS 4628 T , in genus Domibacillus [31]. We were also able to isolate the bacterium Sulfitobacter dubius at the depth of 20 meters.…”
Section: Resultsmentioning
confidence: 65%
“…Additionally, the bacterium Alteromonas macleodii isolated from sediment samples is known to be widespread in the tropical environments as an opportunistic copiotroph harboring the Na + /H + antiporters to survive in high salinity environments [29,30]. We also found a novel bacterium Domibacillus indicus , which was isolated from the depth of 5 meters [31]. This bacterium showed 97.6% 16S rRNA gene sequence similarity with the only other species reported, i.e.…”
Section: Resultsmentioning
confidence: 86%
“…The extraction of genomic DNA of strain ESP3B_9 T was carried out as described previously [12]. Archaeal primer pair 21F (5′-TCCGGTTGATCCYGCCGG-3′) and 1492R (5′-GGTTACCTTGTTACGACTT-3′) [13] was used for 16S rRNA gene amplification by PCR.…”
mentioning
confidence: 99%